DETECTION OF POLLEN FLOW IN THE SEEDLING SEED ORCHARD OF Acacia mangium USING DNA MARKER - Yuskianti, Vivi; Isoda, Keiya (Secretariat of Forestry Research and Development Agency, 2013)
Pollen pattern dispersal in seedling seed orchard (SSO) is an essential part of a tree-improvement program. Two SSOs of Acacia mangium in South Kalimantan and South Sumatra that represent similar resources in different environments were used in this study.Â Genotypes of all trees and seeds from a subset of 10 mother trees in each orchard were determined for 12 microsatellite loci, and parentage analysis was carried out. The results shows that the pollen dispersal pattern in both SSOs decrease with distance from mother tree. Patterns of pollen dispersal, dispersal distance and cumulative frequency of pollen dispersal distance were similar in both SSOs. Random pollen dispersal were found in both SSOs. About 80% of all crosses were found within a 40-m distance range with the most frequent pollination distance between mother tree and male male parents was 0-10 m. No self-pollinated seed was detected. Application of all these aspects found in this study such as random pollen dispersal and the effective pollen dispersal distance can be useful for establishing seedling seed orchard, clonal seed orchard and in other tree improvement activities of A. mangium.